High-efficient and durable overall water splitting performance by interfacial engineering of Fe-doped urchin-like Ni2P/Ni3S2 heterostructure - Chen, Wei-Zhe; Liu, Peng-Yu; Zhang, Lei; Liu, Yang; Liu, Zhiliang; He, Jinlu; Wang, Yan-Qin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
A novel Fe-doped urchin-like Ni2P/Ni3S2 (NPZFNS@C/NF) heterostructure with abundant hetero-interfaces and carbon-coating is successfully constructed, which exhibits outstanding oxygen evolution reaction (OER) performance and excellent hydrogen evolution reaction (HER) performance. Furthermore, it also exhibits a small overpotential of 1.5 V for overall water splitting with NPZFNS/NF as both anode and cathode, lower than most of non-noble metal-based bifunctional electrocatalysts reported. [Display omitted] •Fe-doped Fe-Ni3S2/Ni2P@C/NF hetero-interface electrocatalyst is firstly constructed.•The catalyst shows oustanding OER and excellent HER performances.•It can act as a bifunctional catalyst toward excellent overall water splitting bebavior.•The unique electronic structure of the catalyst is the intrinsic reason for the excellent OER and HER performances.•DFT calculations further reveal the changes the d-band center and the rate-degerming step. Interfacial engineering is an efficient strategy to develop electrocatalysts with excellent performance. By using this strategy, a novel Fe-doped urchin-like Ni2P/Ni3S2 (NPZFNS@C/NF) heterostructure with metal–organic frameworks (MOFs) as the precursor in-suit grows on nickel foam (NF) with abundant hetero-interfaces and carbon-coating is successfully constructed. Owing to the existence of hetero-interfaces and carbon coating, the unique surface electronic structure and d-band center of NPZFNS@C/NF are also obtained. Benefiting from the regulation of electronic structure and d-band center, the NPZFNS@C/NF electrode exhibits extremely high activity for oxygen evolution reaction (OER) and high activity for hydrogen evolution reaction (HER), which shows a very low overpotential of 141 mV at the current density of 10 mA cm−2 for OER and 129 mV for HER respectively in alkaline electrolyte. Furthermore, it also exhibits a small overpotential of 1.5 V for overall water splitting with NPZFNS@C/NF as both anode and cathode, which is lower than most of non-noble metal-based bifunctional electrocatalysts reported. Density functional theory (DFT) results further confirm that the hetero-interface with carbon coating can further optimize Gibbs free energies for both OER and HER processes. This design and constructure strategy provides a new avenue for overall water splitting.